Effects of young corn ear addition on nutritional composition and acceptability of some selected traditional wheat-based local kuih - Nien, Chow Yuh (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Young com ear powder (YCP) was added into three selected traditional wheat-based local kuih namely Kuih Apam, Baidu Cennai and plain cake at the formulations of 5%, 10% and 15%. Kuih with 100% wheat flour and 0% of YCP were the control in this study. The aim of the study was to evaluate the effects of YCP on the nutritional composition, textural properties and sensory attributes of these selected kuih. The present study showed that all the proximate composition of Kuih Apam increased in line with the percentages of YCP. The addition of 15% YCP increased the ash and protein significantly compared to the control (0%). a significant increase in the moisture, ash and fat in Baulu Cermai added with 15% of YCP compared to the control (0%). On the other hand, the addition of YCP into plain cake did not show any predictable trend in the proximate composition. However, addition of 15% YCP had increased the moisture, ash and protein compared to the control (0%). Apart from that, the results indicated that the total dietary fibre content of Baulu Cermai and plain cake increased proportionally with the escalating levels of YCP added. Meanwhile, 10% and 15% of YCP addition in Kuih Apam significantly increased the total dietary fibre content compared to the control (0%). Furthermore, texture profile analysis results showed iv Furthermore, there was that the addition of 15% YCP in Kuih Apam increased the firmness, cohesiveness, springiness, gumminess and chewiness attributes significantly but 15% of YCP addition in Baulu Cermai produced a significantly less chewy sample compared to the control (0%). Meanwhile, the addition of YCP did not affect any of the textural properties significantly. Apart from that, results of sensory evaluation indicated that addition of 15% of YCP in Kuih Apam decreased all the sensory attributes scores significantly. On the other hand, the highest score in flavour and overall acceptance for 10% YCP added Baulu Cermai was observed. The results also showed that 10% of YCP addition in plain cake was the highest percentage preferred by the panellists with the highest scores in chewiness, tenderness and flavour attributes. In a nutshell, 5% of YCP addition in Kuih Apam and 10% of YCP addition in both Baulu Cermai and plain cake can be recommended as a maximum level to enhance the proximate composition and total dietary fibre content of the selected traditional wheat-based acceptability of these kuih. V local kuih without jeopardizing the textural properties and the consumers’